Mythologies of Outer Space ... - Humble, Noreen; Ellis, Jim (University of Calgary Press, 2025)
Every culture and society has read stories in the night sky. From the careful attention of astronomers across all times and all parts of the world to the search for alien life, the stories found in the shapes of constellations to the expansive imaginings of science fiction, there has always been life up there, at the very least, for our imaginations. Mythologies of Outer Space brings together academics and artists to explore diverse imaginings of outer space. It examines questions that, in a world where outer space is increasingly accessible, are no longer only science fiction. Is outer space terra nullius, open for settlement? What if there is life beyond earth? Will we repeat the mistakes of the colonial age on other planets? Should parts of outer space be protected, like nature reserves? What about resource extraction? Do celestial bodies, like the moon, have rights? Astronaut Robert Thirsk, Mi’kmaw astronomer Hilding Neilson, digital humanities scholar Chris Pak, and outer space archaeologist Alice ...